The rise of the Novel in Kazakh literature (Eurasian Journal of Philology Science and Education, 2022)
As one of the most important literary genres, the novel of new characteristics first emerged in Kazakh literature at the beginning of the twentieth century. However, early Kazakh novels have been questioned for their short length and immaturity in composition over the years. In the Soviet period, some scholars even suggested that the works before the October Revolution, such as Jamal the Unfortunate, Kalyn Mal, Girls Let’s Have a Look, Beautiful Kamar and Sorrowful Mariam were not novels in real terms. In response to these questions, our article attempts to reinterpret prerevolutionary Kazakh novels from a new perspective and reveal their unique artistic value. With the help of Ian Watt and Michael Mckeon’s theories of the novel, our article re-examines the prerevolutionary Kazakh novels in terms of narrative, language, and thoughts, using historical and inductive methods. Our textual analysis proves that realistic narrative, prose language, and enlightenment thoughts are the main contributions of prerevolutionary Kazakh novels to Kazakh literature and the fundamental reasons they can be recognized as novels. Key words: prerevolutionary Kazakh novels, Kazakh literature, enlightenment thoughts, realism